Relationships between Service Quality, Service Marketing Mix, and Behavioral Intention: Consumers’ Perspectives on Short-term Accommodation Service for Tourism in Thailand - et. al., Nattapat Manirochana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to examine the degree of perceived service quality, service marketing mix, and behavior intention of tourists in Thailand. It also studies the relationship between service quality and service marketing mix on behavioral intention of tourists using Thailand’s short-term accommodation service. Research methods used in this study is questionnaire, with 5-point Likert scales. The targeted samples are 1,540 tourists who have used short-term accommodation service in Thailand. 1,127 questionnaires were completed and returned, making up 73.18% of all questionnaires distributed. Collected data were analyzed using both descriptive and inferential statistics. The former includes means and standard variations which were used to determine the degree of each variables. The latter includes Pearson correlation analysis for the analysis of relationships between variables. The study shows that the overall service quality and behavioral intention were rated as high, with overall marketing mix rated at the highest level. As for correlations, service quality is found to be moderately and positively correlated with behavioral intention. A similar moderate and positive correlation is found between service marketing and behavioral intention. All variables are statistically significant at the .01 level.